Management of Complications Related to Removal of the Buccal Fat Pad - Pimentel, Thais [UNESP]; Hadad, Henrique [UNESP]; Statkievicz, Cristian [UNESP]; Alcantara-Júnior, Albertino Gomes de; Vieira, Eduardo Hochuli [UNESP]; Souza, Francisley Ávila [UNESP]; Garcia-Júnior, Idelmo Rangel [UNESP] (Wolters Kluwer, 2021)
ABSTRACT: Removal of the buccal fat pad (BFP) is an important topic of discussion in the literature. Several studies have reported improvements in facial esthetics as a result of this technique. The BFP is close to vital structures, such as the facial nerve, parotid duct, and vessels. Injuries related to these structures may occur during the surgical procedure. This manuscript aimed to report and discuss 2 clinical cases of the complications after removal of the BFP. Besides the case presentation, a comprehensive review of the literature was also provided. The reported cases were 2 patients aged 31 and 38 years who were attended by the oral and maxillofacial surgery teams after a complication in the BFP surgery. The first case involved swelling due to Stensen's duct injury, and the second involved uncontrolled bleeding from the internal maxillary artery. Removal of the BFP must have precise indications. Complications may occur during or after surgery; hence, anatomical knowledge is fundamental to appropriate patient management.